Military Service Member Perspectives About Occupational Therapy Treatment in a Military Concussion Clinic. (October 2019) - Cogan, Alison M.; Huang, Janice; Philip, Joyce
The purpose of this study is to describe important features of occupational therapy practice for treatment of military service members with chronic symptoms and a history of mild traumatic brain injury (mTBI) in a military concussion care clinic from service members' perspectives with support from occupational therapy practitioners. Two series of focus groups were conducted with service members with chronic mTBI-related symptoms ( n = 6) and practitioners ( n = 5). Data were analyzed concurrently with collection. We identified five main themes: therapeutic relationship, consistent inclusion of family members, combat versus noncombat injuries, loss of military identity, and assessment against population norms. The findings of this study suggest that service members' evaluations of occupational therapy are based on the overall experience of the encounter, centered by the therapeutic relationship, rather than specific intervention strategies or technology.